Green Human Resource Management Practices in Hospitality Industry: A General Review - I Gede Rai Palguna (International Journal of Glocal Tourism, 2021)
Abstract: Purpose: This article aims to explore the concept of Green Human Resource Management (HRM), the Green HRM model, and the practice of Green HRM implementation in the hospitality industry. Research methods: This study used a qualitative descriptive method with literature review. The article was taken as study material using the Google Scholar search engine. Findings: Human resource managers must have a good awareness of the Green HRM concept, after which Green HRM practices can be carried out, such as: green building concepts, minimizing paper use, recycling and disposal of waste, and energy conservation. They should clearly integrate the concept of Green HRM in human resource functions. Implication: Employees are expected to have a vision of sustainability, which is in the end company also concentrates not only on economic sustainability, but also ecology, and the social environment.